An Overview of Mother's Knowledge about Prevention of Stunting on Toddlers at Kasih Bunda Clinic Sunggal Deli Serdang Regency 2022 - Hutapea, Rina; Veronika, Anita; Manik, Risda Mariana; Sinaga, Desriati (Sean Institute, 2022)
Stunting is defined as the condition of the nutritional status of toddlers who have a length or height that is classified as less when compared to age. One of the factors that most influence the incidence of stunting in toddlers is mother's knowledge. Mother’s knowledge is very important in preventing stunting in order to create actions or behaviors to avoid stunting in toddler. This study aims to describe the knowledge of mothers about stunting prevention on toddlers the Kasih Bunda Clinic Sunggal, Deli Serdang Regency 2022. This research uses a descriptive method. The sample in this study are mothers who had toddlers aged less than 2 years who make repeated visits to the posyandu at Kasih Bunda Clinic using accidental sampling technique. The location of this research is at Kasih Bunda Clinic on May 2022. With 30 respondents The measuring instrument used is the questionnaire. The results of the study are as follows: the majority of mothers' knowledge about exclusive breastfeeding aged 0-6 months had good knowledge as many as 13 people (43.33%), mother's knowledge about complementary foods according to the recommendation was sufficient knowledge 15 people (50%), mother's knowledge about Nutrition Intervention 7-23 months had good knowledge only 12 people (40%), Mother's knowledge about Growth and Development Monitoring has good knowledge of 13 people (43.33%), mother's knowledge of Environmental Hygiene has sufficient knowledge of 19 people (63.33%). The conclusion of the study is that some respondents have good knowledge about preventing stunting in toddlers at the Kasih Bunda Sunggal Clinic, Deli Serdang Regency. The research site is expected to provide counseling to mothers who have toddlers aged less than 2 years about stunting prevention. Respondents are expected to be able to apply the knowledge they already have in preventing stunting